The Effectiveness of Simulation-Based Team Training in Obstetrics Emergencies for Improving Technical Skills: A Systematic Review. Issue 2 (April 2020) - Yucel, Cigdem; Hawley, Glenda; Terzioglu, Fusun; Bogossian, Fiona
Abstract : Summary Statement: This review explores the effectiveness of simulation-based team training in obstetric emergencies for improving technical skills. A literature search was conducted that included all articles to January 2018. A total of 21 articles were included from a potential 1327 articles. Each included study was assessed for impact of the training program using Kirkpatrick's 4-level model. Only the performance of technical skills was evaluated. Five studies reported on acceptance of simulation as an education tool at a level 1. Level 2 outcomes were reported in 7 studies where staff demonstrated improved skills in an educational setting. Three studies reported improved performance in a clinical setting at a level 3. Ten studies were categorized as level 4 and found that simulation learning was translated into improved techniques or maneuvers in reduced time frames in emergency situations of shoulder dystocia and postpartum hemorrhage. There was evidence that neonatal outcomes were improved. Abstract : Supplemental digital content is available in the text.